Handwashing promotion and the use of hand sanitizer as a preventative measure on the development of bacteria - Suswati, Irma; Maulida, Anisa Putri (Universitas Muhammadiyah Malang, 2020)
A proper handwashing practice in Indonesia is around 49, 8%. A report from Basic Health Research 2018 recorded that Indonesians did not practice proper handwashing. This article aims to determine level of knowledge, number, and type of bacteria on hands. This community service program was conducted to 20 participants of the Regional Office of ‘Aisyiyah Malang through handwashing promotion using cleaners (such as soap, wet tissue, and hand sanitizer) to be applied to media called Nutrients Agar Plate (NAP). Then, the participants were to do gram staining to count number, type, and morphology of bacteria. The method implemented was desciptive data analysis. Finding shows that in the aspect of knowledge level, 75% of the participants were able to answer all questions correctly after the handwashing promotion program. On the count, there were 154 colonies of bacteria growing on unwashed fingers; 8 colonies on the fingers using hand sanitizer; 36 colonies on the fingers washed with soap, and 29 colonies with wet tissue. Handwashing habits provides knowledge to individuals of healthy living behaviour to prevent bacterial growth. It is concluded that hands washed with soap and running water, hand sanitizer, and wet tissue can actually reduce number of bacterial colonies as they contain bactericidal or bacteriostatic chemicals. Types of bacteria from coccus and Gram-positive rods are Staphylococcus, Streptococcus or Corynebacterium.